"Our Ancient Monuments": Visualizing Documents in Stone. Issue 1 (15th May 2019) - Edwards, Elizabeth
Abstract : This article explores the ways in which, during the interwar period, practices of state preservation of ancient monuments in Britain established a visual rhetoric of "monument as document." This was expressed through photographic postcards and the visual presentation of monuments themselves. Informed by an entangled ethos of scientific archaeological understanding, public education, and discourses of public ownership, I argue that photographs established and projected patterns of visibility and legibility, which addressed these core values of preservation, educative interpretation, and public access, within the practices of the "techno‐state."